Are inequalities produced through the differential access to play opportunities at school? A call to level the playing field - Alexander, Stephanie A. (Can J Public Health, 2016)
Children’s play is characterized as pleasurable, but it is also viewed as critical for child health and well-being. Yet over the past decade, play researchers and advocates from various disciplines have suggested that there are decreasing opportunities for children to play, particularly at school. One concern is that the changing play environment in schools is reducing children’s active play options and is thereby contributing to increases in childhood obesity. Building on findings from the Québec Adipose and Lifestyle InvesTigation in Youth (QUALITY), this commentary suggests that while opportunities to engage in physical activity may indeed be differentially shaped by school play environments, physical health may not be the only factor at stake in unequal play environments in schools. While this is not an altogether new concern, we argue that it is nevertheless important to highlight within physical activity research settings that children’s overall well-being, including their experience of pleasure, creativity, imagination and sociability, is also shaped by a school’s play environment. Addressing possible inequalities in children’s experience of play in schools, we propose several questions and future research directions for addressing children’s health and well-being in the school environment.